The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/wer.1575
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced volatile fatty acids accumulation in anaerobic digestion through arresting methanogenesis by using hydrogen peroxide

Abstract: Volatile fatty acids (VFAs) can be accumulated as a final product of anaerobic digestion via arresting methanogenesis. Herein, hydrogen peroxide (H2O2) was studied to inhibit methanogenesis for enhancing VFA accumulation with glucose as a substrate. The addition of 0.06 wt.% H2O2 significantly reduced methane production and led to a VFAs concentration of 1233.1 ± 55.9 mg L−1, much higher than 429.3 ± 5.6 mg L−1 in the control that did not have H2O2 addition. The dominated VFAs with H2O2 were acetic acid and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This observation is consistent with the finding that these substrates also had the highest SUM-VFA concentrations (Table 4). Despite the possibility of inhibition due to the high SUM-VFA concentration, it was not observed during the experiments because the inoculum used had a high buffer capacity [51][52][53][54][55].…”
Section: Energy Balancementioning
confidence: 99%
“…This observation is consistent with the finding that these substrates also had the highest SUM-VFA concentrations (Table 4). Despite the possibility of inhibition due to the high SUM-VFA concentration, it was not observed during the experiments because the inoculum used had a high buffer capacity [51][52][53][54][55].…”
Section: Energy Balancementioning
confidence: 99%
“…Hydrothermally treated thickened waste-activated sludge 1.53 [38] Glucose (methanogenesis inhibition using H 2 O 2 ) 1.23 [39] Food waste (methanogenesis inhibition using 2-bromoethanesulfonate) 0.8 [40] Pretreated corn stover (methanogenesis inhibition using 2-bromoethanesulfonate) 2.19 [41] Pulp sludge torrefaction condensate (methanogenesis inhibition using 2-bromoethanesulfonate) 1.1-4.78 This study…”
Section: Substratementioning
confidence: 99%
“…Evaluations of sludge extent of digestion can be made from its volatile solids content and its ability to dewater [19]. Studies also reported that inoculum pretreatment of sludge can regulate the volatile fatty acid accumulation [20]. Anaerobic biodegradation is a complex process involving many microbial steps that are conducted by different groups of bacteria, and the toxicity that occurs during anaerobic treatments typically occurs as a result of the incubation of methanogenic/acetogenic bacteria.…”
Section: Degradation Capability Of Aerated Leachate In Anaerobic Systemmentioning
confidence: 99%